Efektivitas E-Recruitment dan Media Sosial Dalam Meningkatkan Minat Pelamar Kerja Generasi Z - Ruly Hardiansyah; R Deni Muhammad Danial; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2023)
According to the Central Bureau of Statistics (BPS) of Sukabumi City, the population aged 15 and over is the working-age population. The total labor force in Sukabumi City was known to have increased to 56.86 million in January 2021, compared to 55.74 million in January 2020. The labor force included unemployed persons over the age of 15 who were the employed or employed but temporarily jobless and the unemployed. The research was aimed at determining whether e-recruiting and social media had a significant influence towards increasing Gen Z's willingness to apply for jobs, and evaluating the effectiveness of social media and e-recruiting in evoking the interest in applicants among the Gen Z students in Sukabumi. The primary research data were obtained from respondents and conducted quantitatively using associative descriptive method. The data, collected through questionnaires, consisted of 27 questions. The sample used consisted of 100 higher education students served as respondents from 10 universities in Sukabumi City by means of cluster sampling technique. Likert scale was deployed and multiple linear regression analysis was used for processing the data. Research Findings; e-recruitment and social media have a positive influence on increasing Gen Z job-seeking enthusiasm. Keywords : E-Recruitment, Social Media, Interest in Applying for a Job